The eddy current induced in the pulsed bump magnet for the CSNS/RCS injection - 宋金星 康文 霍丽华 郝耀斗 王磊 (Chinese physics C, 2011)
The injecton pulsed bending bump magnets of Rapid Cycling Synchrotron （RCS） in China Spalla- tion Neutron Source （CSNS） consist of four horizontal bending （BH） magnets and four vertical bending （BV） magnets. The BH magnets are operated at a repetition rate of 25 Hz and are excited with a trapezoid rectangle waveform with about 1.6 milliseconds duration. The eddy current is induced in BH magnets and in the end plates it is expected to be large, so the heat generation is of our great concern. In this paper, the eddy current loss of the BH magnet has been investigated and calculated by using a coupling method of 3D electromagnetic and thermal analysis. The accuracy of the analysis is confirmed by testing the prototype BH magnet. The end plate temperature of the BH magnet provided with slit cuts has been decreased obviously and met the requirements.